Программирование с экспрессией генов: модификации эволюционного процесса - Руденко, О.Г.; Мирошниченко, С.В.; Бессонов, А.А. (Управляющие системы и машины, 2015)
Проанализированы некоторые модификации эволюционного процесса, используемого в программировании с экспрессией генов, направленные на улучшение свойств традиционного алгоритма. Результаты экспериментов свидетельствуют о том, что использование рассмотренных модификаций позволяет существенно повысить качество решений. Дальнейшие исследования целесообразно направить на разработку эффективных методов многопроцессорной реализации алгоритмов программирования. Проаналізовано деякі модифікації еволюційного процесу, який застосовується у програмуванні з експресією генів і спрямовані на покращення властивостей традиційного алгоритму. Результати експериментів свідчать про те, що використання розглянутих модифікацій дозволяє суттєво підвищити якість розв’язків. Подальші дослідження доцільно спрямувати на розробку ефективних методів багатопроцесорної реалізації алгоритмів програмування. Based on the analysis and modeling results of the existing implementations of gene expression programming algorithm (GEP), a number of performance limitations of the standard algorithms such as duration of the fitness computation, lack of the numerical constants fine-tuning, impact of size on the rate of chromosome convergence and some other problems related to finding complex models have been identified. In this paper some modifications of the evolutionary process that is used in the GEP to improve the properties of the conventional algorithm were analyzed. For example, it is proposed to use chromosomes with a variable number of genes and with a variable size of each gene. This approach has led to halving of the gene length and, consequently, the size of the solutions' syntactical trees. It is shown that the implementation of the traditional algorithm requires considerable computing resources. To speed up the process it is proposed to use such a computer resource as multiple processors. For automated parallelization of software it is recommended to use the library that implements OpenMR standard. The experimental results indicate that the use of the considered modifications often helps to achieve significant improvement in the quality of the solutions. It seems appropriate to direct further research to development of the effective methods for implementation of multiprocessor GEP algorithms.